Context of mutations within the Romanian agricultural sector - Ioan-Niculae Alecu; Gyorgy Szabo; Caroly Nagy; Irina Angelescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
This paper represents an analysis of the way in which the potato-growing areas and yields obtained in Covasna County have evolved, compared to the situation existent at national level. In the introduction and in the first part of the paper, the global and European situation is also mentioned, taking into account the special importance of potato in the human diet in different areas of the world. The period between 2006 and 2014 is analysed, with a special focus on the situation existent in 2014 and with references to the national situation, as it was mentioned before. The evolution of potato-growing areas and yields is also analysed, in comparison with other crops in the production structure of the county, with the aim to explain the meaning of this evolution and taking into account the special importance this crop has always had in the economy of the county. Although the potato-growing areas in the Covasna County have registered, similar to the national situation, a sharp decline, potato continues to have a special significance in the agricultural economy of the county, as well as in the agricultural economy of the entire country, that continues to be ranked the third place among the potato-growing countries at the European level.
Keywords: 330; potato; cropped areas; yields; area diminishing; climatic conditions